1989
DOI: 10.1016/0014-5793(89)80198-x
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic acid, a specific protein phosphatase inhibitor, induces maturation and MPF formation in Xenopus laevis oocytes

Abstract: Micro-injection of, or incubation with okadaic acid (OA), a specific phosphatase inhibitor, can induce formation of maturation-promoting factor (MPF) and germinal vesicle breakdown (GVBD) in Xenopus laevis oocytes. Comparison of the dose-response curves of OA on maturation, isolated enzymes and phosphatase activities in crude oocyte preparations suggests that inhibition of both polycation-stimulated (PCS) and ATP,Mg-dependent (AMD) phosphatases is sufficient but requires that a critical phosphorylation level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
116
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(120 citation statements)
references
References 28 publications
4
116
0
Order By: Relevance
“…Because PP1s are highly conserved among different species, we decided to determine whether the inhibitory role of PfLRR1 on PP1 could be operative in cells. To address this point, we used Xenopus oocytes that are physiologi-cally arrested in G2/M prophase I and in which OA, a specific protein phosphatase inhibitor, induces GVBD (Goris et al, 1989). We observed that the microinjection of PfLRR1 to oocytes, similar to anti-PP1 antibodies and OA, promoted the progression of oocytes to M phase, inducing GVBD.…”
Section: Discussionmentioning
confidence: 99%
“…Because PP1s are highly conserved among different species, we decided to determine whether the inhibitory role of PfLRR1 on PP1 could be operative in cells. To address this point, we used Xenopus oocytes that are physiologi-cally arrested in G2/M prophase I and in which OA, a specific protein phosphatase inhibitor, induces GVBD (Goris et al, 1989). We observed that the microinjection of PfLRR1 to oocytes, similar to anti-PP1 antibodies and OA, promoted the progression of oocytes to M phase, inducing GVBD.…”
Section: Discussionmentioning
confidence: 99%
“…OA has been shown to activate latent cdc2 kinase in oocytes and early embryos (7,13,22). Since OA increased cdc2 kinase to some extent in metaphase extracts before cyclin protease was activated (Fig.…”
mentioning
confidence: 88%
“…In G2-arrested oocytes, cdc2 kinase is maintained in an inactive form due to phosphorylation of its catalytic subunit (6,11,14,18,20). OA has been shown to induce both dephosphorylation and activation of cdc2 kinase in starfish oocytes (22), and both events probably also occur in amphibians (7,13). The cdc2 phosphatase is not known, but it shares many features in common with phosphatase X: it is not sensitive to OA, does not require Ca2+, and is activated either by blocking type 2A phosphatase or by microinjecting the pure cdc2 kinase (5) (the so-called MPF amplification process).…”
mentioning
confidence: 99%
“…2), compounds known to be inhibitors of PP2A [35-381. All the PTPases tested so far were insensitive towards okadaic acid [35,441, with the exception of the PTPase activity of PP2A, which was shown to be as sensitive towards okadaic acid as its Ser/Thr phosphatase activity [15, 36,451. Based on these findings, it is highly probable that the phosphatase has dual specificity.…”
Section: T-antigen-associated Pp2a Shows Okadaic Acid-sensitive Tyrosmentioning
confidence: 99%